2001
DOI: 10.1074/jbc.m009674200
|View full text |Cite
|
Sign up to set email alerts
|

Zonula Occludens Toxin Structure-Function Analysis

Abstract: Zonula occludens toxin (Zot) is an enterotoxin elaborated by Vibrio cholerae that increases intestinal permeability by interacting with a mammalian cell receptor with subsequent activation of intracellular signaling leading to the disassembly of the intercellular tight junctions. Zot localizes in the bacterial outer membrane of V. cholerae with subsequent cleavage and secretion of a carboxyl-terminal fragment in the host intestinal milieu. To identify the Zot domain(s) directly involved in the protein permeati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 182 publications
(65 citation statements)
references
References 28 publications
1
64
0
Order By: Relevance
“…Experiments were carried out as we have described (17,19,23). Briefly, male BBDP and BBDR rats (age range, 20-110 days) were killed as described above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments were carried out as we have described (17,19,23). Briefly, male BBDP and BBDR rats (age range, 20-110 days) were killed as described above.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we used the combination of the Ussing chamber assay and a recently developed zonulin sandwich ELISA to study whether zonulin was responsible for this early increase in gut permeability typical of BBDP rats (13). Furthermore, we used a synthetic peptide, competitive inhibitor (FZI͞0) (23) to confirm the role of zonulin in T1D pathogenesis and to possibly develop therapeutic and͞or preventive interventions for autoimmune diseases characterized by leaky gut.…”
mentioning
confidence: 99%
“…Although the exact adjuvant mechanism of Zot is not known, it is conceivable that this effect is related to the ability of Zot to open tight junctions, with the subsequent increase in permeability of the mucosal epithelial barrier (9,11,12). It has been reported that Zot may mimic the endogenous molecule zonulin, with which it seems to share a receptor on intestinal epithelial cells (3,26). An octapeptide (FZI/0) homologous to the Zot-zonulin putative binding site that blocks the permeability effects of both Zot and zonulin has been synthesized (3,26).…”
Section: Persistence Of Anti-ova Abs Induced By Zot In Balb/c Micementioning
confidence: 99%
“…It has been reported that Zot may mimic the endogenous molecule zonulin, with which it seems to share a receptor on intestinal epithelial cells (3,26). An octapeptide (FZI/0) homologous to the Zot-zonulin putative binding site that blocks the permeability effects of both Zot and zonulin has been synthesized (3,26). To understand whether the putative …”
Section: Persistence Of Anti-ova Abs Induced By Zot In Balb/c Micementioning
confidence: 99%
See 1 more Smart Citation